2021
DOI: 10.1111/jocd.14492
|View full text |Cite
|
Sign up to set email alerts
|

Description of a safe doppler ultrasound‐guided technique for hyaluronic acid filler in the face—A method to avoid adverse vascular events

Abstract: Background: Knowledge of facial anatomy is essential for professionals intending to inject hyaluronic acid (HA) into that region, but due to the considerable anatomical variations in region, it does not guarantee the complete safety of the procedure.Similarly, procedures widely disseminated among professionals, such as aspiration and the use of cannulas, do not ensure total safety against vascular occlusion events caused by the filler.Objectives: This article describes a technique for injecting hyaluronic acid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(17 citation statements)
references
References 7 publications
0
17
0
Order By: Relevance
“…Doppler ultrasound has been seen to detect anatomy, such as the facial artery lateral to the nasolabial fold, along with its different anatomical variations [109] . One other study commented that although ultrasound may be difficult to manage in conjunction with injection, a new technique combining 3D time of flight magnetic resonance angiography (3D-TOF MOTSA MRA) and infrared (IR) facial heating could visualize the following arteries: facial, angular, superior labial, inferior labial, lateral nasal, dorsal nasal, supratrochlear, supraorbital, and superficial temporal [110] . These images could be acquired on a 1.5 or 3 Tesla (T) system with a head coil, with an additional surface coil on top, to improve signal reception [110] .…”
Section: Mapping Vasculature To Prevent Intravascular Filler Injectionmentioning
confidence: 99%
See 3 more Smart Citations
“…Doppler ultrasound has been seen to detect anatomy, such as the facial artery lateral to the nasolabial fold, along with its different anatomical variations [109] . One other study commented that although ultrasound may be difficult to manage in conjunction with injection, a new technique combining 3D time of flight magnetic resonance angiography (3D-TOF MOTSA MRA) and infrared (IR) facial heating could visualize the following arteries: facial, angular, superior labial, inferior labial, lateral nasal, dorsal nasal, supratrochlear, supraorbital, and superficial temporal [110] . These images could be acquired on a 1.5 or 3 Tesla (T) system with a head coil, with an additional surface coil on top, to improve signal reception [110] .…”
Section: Mapping Vasculature To Prevent Intravascular Filler Injectionmentioning
confidence: 99%
“…One other study commented that although ultrasound may be difficult to manage in conjunction with injection, a new technique combining 3D time of flight magnetic resonance angiography (3D-TOF MOTSA MRA) and infrared (IR) facial heating could visualize the following arteries: facial, angular, superior labial, inferior labial, lateral nasal, dorsal nasal, supratrochlear, supraorbital, and superficial temporal [110] . These images could be acquired on a 1.5 or 3 Tesla (T) system with a head coil, with an additional surface coil on top, to improve signal reception [110] . The authors showed that these MRA images could be projected on the patient's face before injection, albeit without the same 3D depth aspect [110] .…”
Section: Mapping Vasculature To Prevent Intravascular Filler Injectionmentioning
confidence: 99%
See 2 more Smart Citations
“…In mouse and rabbit FIVO models, arterial compression by filler could not be induced and did not result in any prolonged period of significant underperfusion or ischemia [ 110 , 111 ]. In humans, single-point obstructions of facial vessels are easily overcome by a vastly redundant blood supply from adjacent angiosomes, via true anastomoses, which dilate post filler-placement [ 112 ]. Even in instances of bilateral external carotid artery (ECA) ligation, historically performed for intractable epistaxis, compensatory flow from the internal carotid artery (ICA) system has been sufficient to avoid tissue necrosis [ 113 , 114 , 115 ].…”
Section: Pathophysiology Of Ha-mediated Vascular Occlusionmentioning
confidence: 99%